Design of variable bandwidth symmetric/anti-symmetric FIR single-band PCLS lowpass and highpass filters - Ling, B.; Ho, C.; Teo, Kok Lay; Siu, W.; Dai, Q. (2016)
© 2014, Springer-Verlag London. This paper proposes a reconfiguration design of variable bandwidth symmetric/anti-symmetric finite impulse response single-band peak-constrained least squares (PCLS) lowpass and highpass filters. When the bandwidth of the filter changes, a new set of filter coefficients is derived based on the old set of filter coefficients via a modified method of bisection. Since the proposed algorithm is very efficient, the new set of filter coefficients can be obtained in real time. Also, the new set of filter coefficients can be arbitrarily close to the globally optimal solution of the new PCLS optimization problem.